Ferroelectric sensor BaxSr1-xTiO3 integrated with android smartphone for controlling and monitoring smart street lighting - Irzaman, Irzaman; Siskandar, Ridwan; Jenie, Renan Prasta; Syafutra, Heriyanto; Iqbal, Muhammad; Yuliarto, Brian; Fahmi, Mochammad Zakki; Ferdiansjah, Ferdiansjah; Khairurrijal, Khairurrijal (Elsevier B.V., 2022)
In this report, we demonstrated an application of a thin film Barium Strontium Titanate (BST) as a light sensor integrated with an Android smartphone as a model of smart street lighting. BST thin films were fabricated using chemical solution deposition methods followed by spin coating with a variety of mole fractions. We assumed that changes in the lattice parameters of its tetragonal crystal structure caused by variations in the mole fraction result in different ions displacement characteristics that induce charges polarization in the crystal structure. We have confirmed that the BST thin film with mole fraction x = 0.500 was the best thin film for the light sensor in this prototype. Furthermore, it has been found that the smart street lighting gives ∼69.23 % power saving and lower power usage than a conventional street lighting. Additionally, this developed system has successfully reported the lamp status that is to be maintained to an Android phone of the maintainer by using a short message system. This self-reporting makes it easy for maintainer to identify broken lamps and to do repairs. Moreover, implementation of such features to the street lighting can reduce the operating cost.